ARTISTS FROM BUNDELKHAND: COLOR COMBINATION OF KISHAN SONI'S PAINTINGS: बुन्देलखण्ड के कलासाधक: किशन सोनी के चित्रों का रंगसंयोजन - Pathak, Garima (International Journal of Research -GRANTHAALAYAH, 2014)
The art seeker of Bundelkhand, Mr. Kishan Soni ji was born in U.P. It was held in Jhansi district of 19 November 1958. His father Mr. Suraj Prakash Soni was originally Rajasthani but has been living in Jhansi for many years, his mother's name is Mrs. Chanda Soni. In 1975, Soni ji passed the high school examination but under the circumstances he could not study further. Today, by looking at his personality, behavior and knowledge, no one can think that there are few stages of his institutional education left and he is also a true example of the fact that 'art is not an attachment to any schooling and knowledge' Since childhood, Soni ji saw her father embellishing the clothes, so in him, according to the genetic properties, the qualities of an artist automatically came into being. His mother always kept his morale high. Soni ji, in his childhood, learned his father's work of embroidery and started helping him for Dharnjan, but he did not mind in this work. Then he, with the inspiration of his mother, shifted his attention to painting. He made his first person portrait of his 'granny mother'. At this time, he was only 14 years of age. बुन्देलखण्ड के कला साधक श्री किशन सोनी जी का जन्म उ.प्र. के झांसी जिले में 19 नवम्बर सन् 1958 को हुआ। इनके पिता जी श्री सूरज प्रकाश सोनी मूलतः राजस्थानी थे लेकिन कई वर्षों से झांसी में ही रह रहे हैं इनकी माताजी का नाम श्रीमति चंदा सोनी है। सन् 1975 में सोनी जी ने हाई स्कूल की परीक्षा पास की लेकिन परिस्थितिवश वे आगे नहीं पढ़ सके। आज उनके व्यक्तित्व, व्यवहार और ज्ञान को देखकर कोई भी यह नहीं सोच सकता कि उनकी संस्थागत शिक्षा के कुछ चरण बाकी रह गये है और वह इस तथ्य के भी साक्षात् उदाहरण है कि ‘कला किसी भी स्कूली शिक्षा व ज्ञान की मोहताज नहीं’ बचपन से ही सोनी जी ने अपने पिता जी को वस्त्रों को अलंकृत करते हुए देखा अतः उनके अन्दर आनुवांशिकी गुणो के अनुसार एक कलाकार के गुण स्वतः ही आ गए । इनकी माता जी ने इनका मनोबल हमेशा बढ़ाए रखा। सोनी जी ने बालपन में ही अपने पिता जी ने कढाई का काम सीख लिया और धर्नाजन हेतु उनकी सहायता करने लगे परन्तु इस काम में इनका मन नहीं लगा। तब इन्होने अपनी माता जी की प्रेरणा से, चित्रकला की ओर अपना ध्यान केन्द्रित किया। इन्होने अपना प्रथम व्यक्ति चित्र अपनी ‘नानी मां’ का बनाया। इस समय इनकी आयु महज 14 वर्ष की थीं।